Personality changes in patients with vestibular dysfunction - Smith, Paul; Darlington, Cynthia (Frontiers in Human Neuroscience, 2013)
The vestibular system is a sensory system that has evolved to detect linear and angular acceleration of the head in all planes so that the brain is not predominantly reliant on visual information to determine self-motion. Since the vestibular system first evolved in invertebrate species in order to detect gravitational vertical, it is likely that the central nervous system has developed a special dependence upon vestibular input. In addition to the deficits in eye movement and postural reflexes that occur following vestibular dysfunction, there is convincing evidence that vestibular loss also causes cognitive and emotional disorders, some of which may be due to the reflexive deficits and some of which are related to the role that ascending vestibular pathways to the limbic system and cortex play in the sense of spatial orientation. Beyond this, however, patients with vestibular disorders have been reported to experience other personality changes that suggest that vestibular sensation is implicated in the sense of self. These are depersonalisation and derealisation symptoms such as feeling ‘spaced out’, ‘body feeling strange’ and ‘not feeling in control of self’. We suggest in this review that these symptoms suggest that the vestibular system may make a unique contribution to the concept of self through the information regarding self-motion and self-location that it transmits, albeit indirectly, to areas of the brain such as the temporo-parietal junction.